Effects of clinoptilolite addition to colostrum on the concentration of serum proteins, minerals, enzyme activities in neonatal calves - Zarcula, Simona Marc; Mircu, Călin; Bonc, Gheorghe; Kirovski, Danijela; Otavă, Gabriel; Ahmadi-Khoie, Mirela; Tulcan, Camelia (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The objective of our research was to determine the effects of colostrum supplementation with clinoptilolite on concentrations of serum proteins, minerals and enzyme activities in newborn calves. Twenty newborn calves that were divided into control group (n=10) which received colostrum and experimental group (n=10) that received colostrum with 0.5% clinoptilolite added in the first three colostrum meals were studied. Blood samples were collected from jugular vein in vacutainer tubes from all calves prior to colostrum intake and after that, at 24 and 48 h after birth. Samples were analyzed for total protein, albumin, α1-globulin, α2-globulin, ß-globulin, γ-globulin, calcium, phosphorus, magnesium, iron, gamma glutamyltransferase, alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase. Clinoptilolite supplementation had significant effect (p<0.0006) on serum iron concentrations in experimental (27.64±3.78 µmol/l) vs control group (8.93±1.26 µmol/l) after 48h. GGT values were also significantly higher (p<0.04) in E (163.60±26.67 U/l) than in C group (84.01±19.77 U/l) at 48h after parturition. Other parameters analyzed were unaffected by clinoptilolite treatment. Obtained data revealed that colostrum supplemented with clinoptilolite had positive effects on some mineral parameters.